Evaluation of the physical-chemical, microbiological, sensory and functional properties of maize flours (Zea mays) obtained by handmade process of nixtamalization (Agroindustria, Sociedad y Ambiente, 2020)
Maize flour (Zea mays) is one of the principals food items consumed in Venezuela that in spite of its preference at the consumed level, is affected by a diversity of economics factors that reduce its availability in commercial shelves. Before this decrease and the boom of handmade products without commercial quality, it was evaluated the physical-chemical, microbiological, sensory and functional properties of maize flours obtained by handmade process of nixtamalization. For this, there were developed 4 formulations with variations in their cooking time (1.5 and 2 h) and resting time (12 and 24 h) through a conventional nixtamalization process. It was evaluated the water absorption index and water solubility index as well as the pH in the four formulations, and it was chosen the formulation (H1) with a cooking time of 1.5 h and resting time of 12 h, for owning the best functional properties (W.A.I= 4,130g/g; W.S.I=5,00 %; pH=6,19). It was evaluated their physical-chemical properties and microbiological quality, presenting acceptable results compare with the corresponding normative. Also, it was evaluated the sensory acceptability thought an hedonic scale of 5 points, evaluating the texture, kneadness, odor, color and taste between H1 and a commercial flour. The acceptability of H1 varied between 4.0 and 5.0 and the evaluated product presented pleasant sensory characteristics, without differences respect the texture, kneadness and odor, highlighting the color and taste of the same, presenting an alternative method for preparing a product with physical-chemical, functional and sensory properties as well as acceptable microbiological quality for consume.
Keywords: Nixtamalization; flour; process; corn; evaluation